Alternative Christianities - Gallagher, Eugene V. (Nova religio, 2014)
This essay introduces the four articles in this volume by describing how the groups they address constitute “alternative Christianities.” That is, each of the groups discussed draws upon the wealth of symbolic religious capital contained primarily in the Christian scriptures while at the same proposing such innovative understandings of it that they are often considered by both their originators and the broader culture as sufficiently different as to represent distinctive alternatives to the mainstream tradition. Particularly important in the generation of such alternatives is the creative exercise of interpretive ingenuity in reading foundational scriptural texts such as the Hebrew Bible, Christian scriptures, or Mormon canon. These four articles also show how the canonization of multiple examples of religious innovation in scriptural texts retains the power to inspire new and alternative movements throughout history.